Structural Transformation and the Volatility of Aggregate Output in OECD Countries - Lonkeng Ngouana, Constant (Washington, D.C. : International Monetary Fund, 2013)
This paper finds a negative relationship between the employment share of the service sector and the volatility of aggregate output in the OECD-after controlling for the level of financial development. This result reflects volatility differentials across sectors: labor productivity is more volatile in agriculture and manufacturing than in services. Aggregate output would therefore become less volatile as labor moves away from agriculture and manufacturing and toward the service sector. I examine the quantitative role of these labor shifts-termed structural transformation-on the volatility of aggregate output in OECD countries. I first calibrate to the U.S. economy an indivisible labor model in which the reallocation of labor across sectors emerges endogenously from sectoral labor productivity growth differentials. The setup is then used to generate the time path of labor shares in agriculture, manufacturing and services in individual countries. Finally, I perform a set of counterfactual analyzes in which the reallocation of labor across sectors is constrained endogenously. I find that the secular shift of labor towards the service sector was volatility-reducing in OECD countries during 1970-2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet